Identification of Variations in Gravity Anomaly Values in the Geothermal Distribution Area of the Rantau Dedap Region, South Sumatra - Leni, Arezzo Fabio Fentola Parinus Frezo; Alamsyah, Sultan Nanda; Azzahra, Istiqoma (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2024)
This study identifies gravity anomaly values using the gravity method in the Geothermal distribution area of the Rantau Dedap area, anomaly data obtained from the TOPEX satellite. This study is located at coordinates 103.275⁰- 103.6917⁰ East Longitude and 3.9052⁰- 4.2876⁰ South Latitude. Free air and topographic anomaly data obtained were 625 data points along with topographic data. This study aims to support previous study with different methods and aims to support study data, especially in the field of geophysical exploration in looking at the subsurface geological structure of this region based on variations in gravity anomaly values. The Simple Bouguer Anomaly (SBA) obtained was in the range -37.2827 mGal to 34.4800 mGal. The Complete Bouguer Anomaly (CBA) value is -37.0843 mGal to 34.6802 mGal. The estimated value obtained is not too different from the Simple Bouguer Anomaly value so it produces the same contour pattern. Meanwhile, the Regional Anomaly obtained has a value of -36.8 mGal to 39.7 mGal and the Residual Anomaly value range is -16.1 mGal to 9.2 mGal. In the residual anomaly map, it can be seen that the anomaly values are positive and negative, this affects several things such as rock density, position and size of the rocks that produce the anomaly. Based on the results of variations in the magnitude of the gravity anomaly obtained, the results obtained are in very good agreement with the geological conditions of the study area.